HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA MATA PELAJARAN SENI RUPA SMP NEGERI 31 PADANG - Wulan Ramadani, Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the relationship between motivation and student learning outcomes in learning class VIII art in SMP Negeri 31 Padang. This study is a correlational study with product moment correlation analysis techniques. Research data collection techniques are questionnaires and documentation. The correlation test results of the study sample as many as 61 students were r-count 0.300 with sig. (2-tailed) 0.019 while the r-table was 0.248. The value of r-count> r-table (0.300> 0.248) and the value of sig. (2-tailed)> sig-alpha (0.019 <0.05) at the 5% significance level. so the variables of learning motivation and learning outcomes have a significant relationship to the learning of class VIII art at SMP Negeri 31 Padang.Keywords: Learning Motivation, Learning Outcomes, Fine Arts